MOOCs Design: A Conceptual Framework for Continuous Teacher Training in Portugal - Carolina Amado; Nuno Dorotea; Ana Pedro; João Piedade (MDPI AG, 2022)
This paper aims to present a conceptual framework for Massive Open Online Courses (MOOCs) design with regard to continuous teacher training, where a mixed methodology research approach was used. This methodology was structured in two consecutive phases: The first phase adopted a sequential exploratory strategy, where a scoping literature review approach was applied, and analysis content techniques were used to map and analyze the key dimensions in the design of MOOCs. The second phase was based on the concurrent triangulation strategy, where the quantitative data were extracted from 103 questionnaires and the qualitative data were obtained from two mini focus group interviews, which contributed to the development of the framework. Based on the data collected in phase 2, we proposed a framework which is structured in three main dimensions and ten subdimensions: (i) Resources-Human and Technological infrastructure; (ii) Design-Course overview, Target learners, Pedagogical approaches, Goals, Learning materials, content and activities and Assessment activities; and (iii) Organization and monitoring-Accreditation and Data monitoring and evaluation. This paper contributes to the actual state of the art in MOOCs design given the inexistence of frameworks for such courses in the specific case of continuous teacher training, and it shows the importance of accreditation recognition by the Portuguese entities.